Indigenous American species of the Bemisia tabaci complex are still widespread in the Americas - Barbosa, Leonardo da F. [UNESP]; Marubayashi, Julio M. [UNESP]; De Marchi, Bruno R. [UNESP]; Yuki, Valdir A.; Pavan, Marcelo A. [UNESP]; Moriones, Enrique; Navas-Castillo, Jesus; Krause-Sakate, Renate [UNESP] (Wiley-Blackwell, 2014)
Bemisia tabaci is a complex of at least 36 putative cryptic species. Since the late 1980s, the Middle East-Asia Minor 1 species (MEAM1, formerly known as the B biotype), has emerged in many tropical and subtropical regions of the world and in some areas has displaced the indigenous populations of B. tabaci. Based on analysis of the mtCOI gene, two indigenous species native to America have been reported: New World (NW, formerly the A biotype) and New World 2 (NW2). NW is present at least in Argentina, Brazil, Martinique, Mexico, Texas and Venezuela, and NW2 in Argentina, Bolivia and Brazil. Wild plants (Euphorbia sp. and Ipomoea sp.), as well as important crops such as tomato, bean and cotton, are still hosts for native B. tabaci populations in the Americas. MEAM1 has not completely displaced the native B. tabaci from the Americas. (C) 2014 Society of Chemical Industry
Keywords: Bemisia tabaci; mtCOI gene; New World; phylogeny; whiteflies